Anestesia multimodal para substituição de válvula mitral num doente com um feocromocitoma - Portela, Filipa; Rato, André (Revista da Sociedade Portuguesa de Anestesiologia, 2024)
Pheochromocytomas are rare neuroendocrine tumours that produce and store catecholamines. Intraoperatively, the release of excessive amounts of catecholamines can produce life-threatening cardiovascular complications. This is a case report of a woman in her 60s recently diagnosed with a pheochromocytoma in need of a mitral valve replacement due to anterior leaflet prolapse and ruptured chord. Due to the possibility of worsening mitral regurgitation and cardiovascular collapse after a hypertensive crisis during adrenalectomy we prioritised the cardiac surgery. Intraoperatively, we performed a multimodal total intravenous anaesthesia with propofol and low-dose infusions of remifentanil and dexmedetomidine. Hemodynamic stability was maintained throughout the procedure and two months later the patient underwent a laparoscopic adrenalectomy uneventfully. Although pheochromocytoma removal is usually a priority surgery, when facing serious cardiovascular pathology, such as severe mitral regurgitation, it may be a better option to prioritise the cardiac surgery over the pheochromocytoma removal.